IMPLEMENTATION OF REUSABLE PACKAGING IN THE AUTOMOTIVE INDUSTRY: CASE STUDY - Nunes, Fabiano de Lima; Rocha, Mauro Vinicius; Sellitto, Miguel Afonso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This article describes a case study on the replacement of disposable packaging for reusable packaging in the international flow of materials in a auto parts company in the Mercosur. The study concerns the automotive parts exported from Brazil to Argentina by the road modal. Initially, it presents a theoretical review about reverse logistics, returnable packaging and international logistics. The following describes the case, according to the information collected by researchers at the company studied. Describe the facts, investigate the causes that originated and compares the process prior to that contemplates the use of disposable packaging, with a new process, based in returnable packaging. This article aims to answer the following research question: How can it be implemented an international flow of return reusable packaging in the automotive industry? Substantive economic, logistics, and environmental gains were yield.